Rewriting the Nigerian Nation and Reimagining the Lesbian Nigerian Woman in Chinelo Okparanta’s Under the Udala Trees (2015) - Serón Navas, Ariadna (Miscelánea: A Journal of English and American Studies, 2021)
This paper presents a revised paradigm of the postcolonial Nigerian nation through the exploration of the figure of the black lesbian in Nigeria. I argue that the reconceptualisation of Nigerian nationhood is enabled through the revision by Chinelo Okparanta in her debut novel Under the Udala Trees (2015) of subaltern and abject Nigerian womanhood carried out from a homoerotic or Afroqueer standpoint. The exploration of lesbian Nigerian woman(hood) from a literary stance clearly represents a valuable and subversive way of re-writing, re-constructing and re-conceptualising the postcolonial Nigerian nation so that othered subjectivities can also become part of the nation-building project. Okparanta, considered an Afrosporic and transcultural writer, interpellates the Nigerian nation in order to present us with post-abyssal configurations that transcend reductive and monolithic discourses. Drawing on the work of a wide array of scholars belonging to Postcolonial, Gender and Queer Studies —such as Neville Hoad, Ifi Amadiume, Lindsey Green-Simms, and Lee Edelman— I demonstrate how Okparanta’s novel can work as an example of resistance against hegemonic, heteronormative and Eurocentric representations of Africa.